The Iraqi Folkloric Tradition of Mājīnā: The 'Trick-or-Treat' of Mesopotamia - Al-Kaisi, Meis (2022)
The term 'trick-or-treat' conjures up the image of Halloween’s festive celebrations. However, similar traditions are also witnessed and practised in some Middle Eastern cultures. The Gulf region in general and Iraq more specifically have a long history of folkloric practices that involve children wandering the streets and asking for treats during the months of Shaban and Ramadan of the lunar calendar. In Iraq it is called mājīnā and in the United Arab Emirates ḥagg el-lēla, plus a variety of other names across the Arabian Gulf. This article examines the Iraqi mājīnā tradition. Scholarly sources on mājīnā are scarce; hence, this article is based mainly on information gathered from Iraqi informants and online magazine articles. The objective is to discuss, record, and preserve the Iraqi mājīnā, which has been thus far largely neglected.